Improving dewaterability of waste activated sludge by thermally-activated persulfate oxidation at mild temperature. (1st March 2021) - Ruan, Shuyu; Deng, Jing; Cai, Anhong; Chen, Shengnan; Cheng, Yongqing; Li, Jun; Li, Qingsong; Li, Xueyan
Abstract: The mass production of waste activated sludge in wastewater treatment plants may lead to environmental pollution and sludge dewatering is an essential process during its treatment. The oxidation of extracellular polymeric substances (EPS) was the core step to achieve deep sludge dewatering. In this study, thermally-activated sodium persulfate (SPS) process was managed to improve the dewaterability of waste activated sludge (WAS) and its internal mechanism was systematically elaborated. Experimental results showed that with 2.0 mmol/g VSS SPS at 80 °C, capillary suction time (CST) was roughly 59.74% of that in raw sludge. Under this condition, 14.66 ± 0.10 × 10 11  kg/m of specific resistance to filtration (SRF) and 61.8% ± 0.1% of water content ( W C ) was determined, respectively. A solubilization/oxidation process was proposed to unravel the mechanism of the enhanced dewaterability of WAS in thermally-activated SPS process. Mild temperature efficiently disrupted the sludge flocs and broke cell walls, releasing large amounts of EPS into bulk phase. Meanwhile, mild temperature accelerated the decomposition of SPS to generate sulfate radicals ( SO 4 − ) and hydroxyl radicals (OH) for oxidizing EPS, facilitating the conversion of bound hydrated water into free water and achieving solid-water separation. The higher reaction temperature favored sludge dewatering, whereas overdosing SPS posed no significant impact. Further analysis illustrated that tyrosine protein-like, tryptophan protein-like, fulvic acid-like and humic acid-like substances in various EPS fractions together exerted the influence on sludge dewatering. Furthermore, the synergy process could alter the secondary structure of protein, which caused a loose structure of EPS and the exposure of hydrophobic sites, facilitating the dehydration of sludge flocs. The details of how thermally-activated SPS process enhanced sludge dewaterability provided the theoretical and technical basis for the application of the process under a real-world situation. Graphical abstract: Image 1 Highlights: Thermally-activated SPS showed an excellent synergetic effect, achieving deep dewatering of WAS. Higher reaction temperature favored WAS dewatering, while overdosing SPS posed insignificant impact. The contribution to dewaterability enhancement was in the sequence of OH >  SO 4 −  > thermal effect. Thermally-activated SPS oxidized functional groups, decomposed EPS and altered protein conformation of EPS.